The world is flat : a brief history of the twenty-first century - Friedman, Thomas L. (New York : Picador, 2007)
Presents an update on globalisation, its opportunities for individual empowerment, its achievements at lifting millions out of poverty, and its drawbacks - environmental, social, and political. Includes stories and insights to help understand the flattening of the world as well as a chapter on how to be a political activist and social entrepreneur. Discusses the question of how to manage our reputations and privacy in a world where we are all becoming publishers and public figures.
HOW THE WORLD BECAME FLAT: While I was sleeping ; The ten forces that flattened the world ; The triple convergence ; The great sorting out ; AMERICA AND THE FLAT WORLD: America and free trade ; The untouchables ; The right stuff ; The quiet crisis ; This is not a test ; DEVELOPING COUNTRIES AND THE FLAT WORLD: The Virgin of Guadalupe ; COMPANIES AND THE FLAT WORLD: How companies cope ; YOU AND THE FLAT WORLD: Globalisation of the local ; If it's not happening, it's because you're not doing it ; What happens when we all have dog's hearing? ; GEOPOLITICS AND THE FLAT WORLD: The unflat world ; The Dell theory of conflict prevention ; CONCLUSION: IMAGINATION: 11/9 versus 9/11.
Includes index
ARC
Trim edication
Complimentary copy from Akbar Ali Khan
Keywords: Diffusion of innovations; Information society; Globalization -- Economic aspects; Globalization -- Social aspects